1989
DOI: 10.4153/cmb-1989-002-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Residual Finiteness of Certain Polygonal Products

Abstract: We give examples to show that unlike generalized free products of groups (g.f.p.) polygonal products of finitely generated (f.g.) nilpotent groups with cyclic amalgamations need not be residually finite (R) and polygonal products of finite p-groups with cyclic amalgamations need not be residually nilpotent. However, polygonal products f.g. abelian groups are R, and under certain conditions polygonal products of finite p-groups with cyclic amalgamations are R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…Then G is X * Y-separable whenever H is 1i.T. We note that the above two results are generalisations of Theorem 3.4 in [3].…”
Section: Let G = E * H F Where E F Are H-separable Let S Be a Susupporting
confidence: 70%
See 2 more Smart Citations
“…Then G is X * Y-separable whenever H is 1i.T. We note that the above two results are generalisations of Theorem 3.4 in [3].…”
Section: Let G = E * H F Where E F Are H-separable Let S Be a Susupporting
confidence: 70%
“…Using their result, Brunner, Frame, Lee and Wielenberg [5] determined all torsionfree subgroups of finite index in the Picard group PSL{2, Z [i]). In [3], Allenby and Tang proved that polygonal products of four finitely generated free abelian groups, amalgamating cyclic subgroups with trivial intersections, is residually finite. Kim and Tang [9] showed that certain polygonal products of four nilpotent groups, amalgamating cyclic subgroups with trivial intersections, are residually finite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, polygonal products of groups can be described as follows [3]: Let P be a polygon. Assign a group G v for each vertex v and a group G e for each edge e of P .…”
Section: Preliminariesmentioning
confidence: 99%
“…Since a polygonal product can appear as a subgroup of a group, and then the residual properties of the polygonal product determine the residual properties of the whole group [6, Example 1.1], we are interested in the residual properties of polygonal products. In [3], Allenby and Tang proved that polygonal products of four finitely generated free abelian groups, amalgamating cyclic subgroups with trivial intersections, are residually finite (RF ). And they gave an example of a polygonal product of finitely generated nilpotent -or free-groups which is not RF .…”
Section: Introductionmentioning
confidence: 99%